1988
DOI: 10.1016/0039-6257(88)90052-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of irreversible severe visual loss in the United States in people over 50 years of age. The nonexudative stage includes hard drusen (associated with localized dysfunction of the retinal pigment epithelium [RPE]), soft drusen (associated with diffuse dysfunction of the RPE), and geographic (areolar) atrophy. These fundus changes may predispose the eye to develop the neovascular/exudative stages of AMD. Most patients who develop severe visual loss from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
370
0
21

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 744 publications
(393 citation statements)
references
References 94 publications
1
370
0
21
Order By: Relevance
“…Subretinal exudates also decreased in 8 eyes. Spontaneous regression has been reported to occur in approximately 20% of patients with ARMD (Bressler et al 1988a(Bressler et al , 1988bPoliner et al 1986;Chandra et al 1974), so the outcome of the clinical series reported here is clearly better compared to the natural progression of the disease. The patients in our study who showed regression or complete disappearance of CNV had relatively small size and little involvement of the macula and CNV within one-half the optic disk diameter from the foveola.…”
Section: Discussionmentioning
confidence: 77%
“…Subretinal exudates also decreased in 8 eyes. Spontaneous regression has been reported to occur in approximately 20% of patients with ARMD (Bressler et al 1988a(Bressler et al , 1988bPoliner et al 1986;Chandra et al 1974), so the outcome of the clinical series reported here is clearly better compared to the natural progression of the disease. The patients in our study who showed regression or complete disappearance of CNV had relatively small size and little involvement of the macula and CNV within one-half the optic disk diameter from the foveola.…”
Section: Discussionmentioning
confidence: 77%
“…13 Pathogenesis of choroidal neovascularization in ARMD involves a complex interplay of environmental, biochemical changes, and genetic predisposition. 14 Hcys has been shown to undergo autoxidation in the presence of transition metal ions like iron which culminates in the generation of hydroxyl radical (OH K ).…”
Section: Discussionmentioning
confidence: 99%
“…8 The majority of patients with severe vision loss (defined as a loss of 6 or more lines of visual acuity) due to AMD have the neovascular form of the condition, which is characterised by choroidal neovascularisation (CNV). 9,10 Vision loss is more likely to be severe in patients with lesions that lie under the foveal avascular zone (subfoveal lesions) than in those that lie outside the fovea. New treatment modalities, such as photodynamic therapy with verteporfin (Visudyne s , Novartis Pharma AG, Basel, Switzerland), have increased the range of treatments available for patients with subfoveal CNV due to AMD.…”
Section: Introductionmentioning
confidence: 99%